Undiversified : the big gender short in investment management - Carr, Ellen (Portfolio manager); Dudley, Katrina (Heilbrunn Center for Graham & Dodd Investing Series, 2021)
"Diversification is a core principle of investing. Yet money managers have not applied it to their own ranks. Only around 10 percent of portfolio managers-the people most directly responsible for investing your money-are female, and the numbers are even worse at the ownership level. What are the causes of this underrepresentation, and what are its consequences-including for firms' and clients' bottom lines? In Undiversified, experienced practitioners Ellen Carr and Katrina Dudley examine the lack of women in investment management and propose solutions to improve the imbalance. They explore the barriers that subtly but effectively discourage women from entering and staying in the industry at each point in the pipeline. At the entry level, the lack of visible role models discourages students from considering the field, and those who do embark on an investment management career face many obstacles to retention and promotion. Carr and Dudley highlight the importance of informal knowledge about how to navigate career tracks, without which women are left at a disadvantage in an industry that lionizes confidence. They showcase a diverse constellation of successful female portfolio managers to demystify the profession. Drawing on wide-ranging research, interviews with prospective, current, and former industry practitioners, and the authors' own experiences, Undiversified makes a compelling case that increasing the number of women could help transform active investment management at a time when it is under threat from passive strategies and technological innovation"--